Resistance-Guided Antimicrobial Therapy Using Doxycycline–Moxifloxacin and Doxycycline–2.5 g Azithromycin for the Treatment of Mycoplasma genitalium Infection: Efficacy and Tolerability. (20th October 2019) - Durukan, Duygu; Read, Tim R H; Murray, Gerald; Doyle, Michelle; Chow, Eric P F; Vodstrcil, Lenka A; Fairley, Christopher K; Aguirre, Ivette; Mokany, Elisa; Tan, Lit Y; Chen, Marcus Y; Bradshaw, Catriona S
Abstract: Background: Macrolide resistance in Mycoplasma genitalium (MG) exceeds 50% in many regions, and quinolone resistance is increasing. We recently reported that resistance-guided therapy (RGT) using doxycycline followed by sitafloxacin or 2.5 g azithromycin cured 92% and 95% of macrolide-resistant and macrolide-susceptible infections, respectively. We present data on RGT using doxycycline–moxifloxacin, the regimen recommended in international guidelines, and extend data on the efficacy of doxycycline–2.5 g azithromycin and de novo macrolide resistance. Methods: Patients attending Melbourne Sexual Health Centre between 2017 and 2018 with sexually transmitted infection syndromes were treated with doxycycline for 7 days and recalled if MG-positive. Macrolide-susceptible cases received 2.5 g azithromycin (1 g, then 500 mg daily for 3 days), and resistant cases moxifloxacin (400 mg daily, 7 days). Test of cure was recommended 14–28 days post-antimicrobials. Results: There were 383 patients (81 females/106 heterosexual males/196 men who have sex with men) included. Microbial cure following doxycycline–azithromycin was 95.4% (95% confidence interval [CI], 89.7–98.0) and doxycycline–moxifloxacin was 92.0% (95% CI, 88.1–94.6). De novo macrolide resistance was detected in 4.6% of cases. Combining doxycycline–azithromycin data with our prior RGT study (n = 186) yielded a pooled cure of 95.7% (95% CI, 91.6–97.8). ParC mutations were present in 22% of macrolide-resistant cases. Conclusions: These findings support the inclusion of moxifloxacin in resistance-guided strategies and extend the evidence for 2.5 g azithromycin and presumptive use of doxycycline. These data provide an evidence base for current UK, Australian, and European guidelines for the treatment of MG. Abstract : Mycoplasma genitalium is challenging to cure due to increasing resistance to antimicrobials. Resistance-guided therapy using doxycycline followed by azithromycin or moxifloxacin achieves high levels of microbiological cure (>92%) and low levels of de novo resistance.